THE INFLUENCE OF COST OF PRODUCTION FULL COSTING AND VARIABLE COSTING METHODS ON SALES RESULTS (CASE STUDY IN KRIPIK CUMI COMPANY IN BANGKA DISTRICT) - Jufri Sani Akbar; Nadia Sri Rezeki (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This research aims to determine the effect of the cost of production using the full costing method and variable costing on sales results at Kripik Cumi company in Bangka Regency. The approach used in this research is a comparative approach which intends to compare different conditions to a problem. The data used are primary data and secondary data, namely data obtained by researchers directly on the object of research and data already available from other parties. Determination of the sample carried out by purposive sampling, namely the sample selected using certain considerations and the number of samples used in this study, data analysis techniques using financial analysis and statistical analysis, financial analysis used in the form of calculating the cost of production, while statistical analysis used are multiple regression and hypothesis testing. The results of the research revealed that the cost of goods manufactured using the full costing method obtained higher yields than the variable costing method. The results of statistical analysis, that the magnitude of the influence of the two costs of production on sales results is 95.2%, and the results of the hypothesis test of the cost of production using the full costing method and the costing variable have a significant effect on sales results, while the results of partial hypothesis testing that have an effect are only price. cost of production of variable costing on sales results, so the company is advised to use the variable costing method Keywords: Full Costing Method, Variable Costing Method and Sales Results